2014
DOI: 10.1111/maec.12150
|View full text |Cite
|
Sign up to set email alerts
|

Does beach seine fishery permanently alter macroinvertebrate communities and sediment characteristics in the Southern Caspian Sea?

Abstract: The impacts of a beach seine fishery on macroinvertebrate communities and sediment characteristics were investigated in the Southwest Caspian Sea. Samples from a single impacted site that was regularly seined were compared with two control sites outside the fishing area. Benthic macroinvertebrates were sampled on four occasions: 6 months prior to the opening of the beach seine fishery (Time 1), 1 day immediately after the closing of beach seining (Time 2), 1 week after closing (Time 3), and 1 month after closi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…These findings align with Nemati et al. (2014) who investigated the impacts of a beach seine fishery on macroinvertebrate communities and sediment characteristics in the Southwest Caspian Sea. They reported that closed season seemed to allow recovery to pre‐closing levels of macroinvertebrate richness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings align with Nemati et al. (2014) who investigated the impacts of a beach seine fishery on macroinvertebrate communities and sediment characteristics in the Southwest Caspian Sea. They reported that closed season seemed to allow recovery to pre‐closing levels of macroinvertebrate richness.…”
Section: Discussionsupporting
confidence: 91%
“…ate statistics) used in the current study have all shown that closed season for beach seine fishing at both study beaches did not only improve species numbers but also richness. These findings align withNemati et al (2014) who investigated the impacts of a beach seine fishery on macroinvertebrate communities and sediment characteristics in the Southwest Caspian Sea. They reported that closed season seemed to allow recovery to pre-closing levels of macroinvertebrate richness.…”
supporting
confidence: 88%